Perfil de glicose por monitorização contínua de mulheres portadoras de diabetes mellitus gestacional comparado ao de gestantes não diabéticas - Marina Pimenta Carreiro (2014)
This dissertation characterizes the profile of glucose in women during the second half of pregnancy, through 72-hours of continuous monitoring using the Medtronic Minimed CGMS® device, and compares non-diabetic gravidas (NDM) with those with gestational diabetes mellitus (GDM). 33 women between 18 and 42 years of age, in the second half of pregnancy were studied, all with a prepregnancy body mass index (BMI) 35kg/m2, 11 with normal glucose metabolism and 22 with GDM. Of the 22 women with GDM, 11 had had free diets (group GDM1) and 11 had received dietary guidance (group GDM2). The groups glucose profiles were then characterized and compared. The characteristics studied were: general pool of glucose measurements and time comparison, fasting glucose, nocturnal glucose, glucose before meals (breakfast, lunch and dinner), glucose after meals (1 and 2 hours), glucose between meals, peak value of glucose after meals, time to glucose peak after meals, percentage of time in relation to the glucose ranges of <60mg/dl, 60-140mg/dl and >140mg/dl, glucose exposure given by the area under the curve, variability of glucose given by the amplitude, standard deviation and interquartile range, which were compared using the likelihood test and a model adjustment of linear regression with random effects or the Kruskal-Wallis or ANOVA tests as appropriate. Most women of the DMG groups had oral glucose tolerance test (OGTT) fasting glucose < 95mg/dl, suggesting mild GDM. Gravidas with GDM exhibited glucose above 140mg/dl more often than non-diabetics (p<0,05). The nocturnal glucose, fasting glucose and the glucose before meals did not differ significantly between the groups. With regard to glucose between meals, it was higher in the GDM1 group than in the NDM group between breakfast and lunch (p<0,05). Similarly the glucose 1 and 2 hours after breakfast and dinner was greater in the GDM1 group than in the NDM group (p<0,05 for all comparisons). However after lunch there was no significantly difference between the groups. The variability of glucose was higher in the GDM1 group than in the NDM group for the three measurements evaluated (p<0,05 for all comparisons), despite no significantly difference was evidenced in glucose exposure given by the area under the curve. Therefore continuous glucose monitoring showed that this group of pregnant women with mild GDM and free diets showed different glucose behaviors compared to the NDM group in levels above 140mg/dl (p<0,05) and in all measurements of variability (p<0,05), which was not detectable by total glucose exposure given by the area under the curve.